A Case of Adenomyosis with a High Titer of IgG Autoantibody to Calreticulin - Neil M. Gude BSc, MSc, PhD; Janet L. Stevenson BSc; Penelope M. Sheehan MB BS, RANZCOG, GDEB; Shaun P. Brennecke MB BS, BA, BMedSci (Hons) (SAGE Publishing, 2013)
Background . High prevalence of autoantibodies to the calcium-binding, endoplasmic reticulum chaperone protein calreticulin has been reported in various autoimmune and parasitic diseases. It has been reported that adenomyosis is associated with the presence of autoantibodies, in particular to phospholipids; however, it is not known whether it is associated with autoimmunity to calreticulin. Results . A 35-year-old gravida 4 para 4 woman presented with a history of many years of intractable menorrhagia. Histopathological examination of a subsequent hysterectomy specimen revealed a bulky uterus, a poorly developed secretory endometrium with decidualization of the stroma and chronic endometritis, as well as the presence of adenomyosis uteri. IgG autoantibodies to calreticulin were measured in the plasma of this and 234 other patients. Nine (3.8%) patients tested positive. The titer of anticalreticulin IgG autoantibody in the sole case with adenomyosis was approximately 8 times the average of other positive-testing samples. Conclusions . The etiology of adenomyosis is unclear. The presence of a high titer, blocking anticalreticulin autoantibody may directly increase the risk that adenomyosis might develop. It is also possible that the expansion of endometrial glandular tissue, as well as elevated estrogens, during adenomyosis may lead to elevated calreticulin, which induces an autoimmune reaction to it. Further study is required to determine whether there is a significant association between adenomyosis and the prevalence of calreticulin autoantibodies.